2007
DOI: 10.1021/bp060299a
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion Culture of Hybridoma Cells for Hyperproduction of IgG2a Monoclonal Antibody in a Wave Bioreactor‐Perfusion Culture System

Abstract: A novel wave bioreactor-perfusion culture system was developed for highly efficient production of monoclonal antibody IgG2a (mAb) by hybridoma cells. The system consists of a wave bioreactor, a floating membrane cell-retention filter, and a weight-based perfusion controller. A polyethylene membrane filter with a pore size of 7 microm was floating on the surface of the culture broth for cell retention, eliminating the need for traditional pump around flow loops and external cell separators. A weight-based perfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 31 publications
3
35
0
Order By: Relevance
“…Heights measured are shown as three circles piled (5, 12, and 22 mm above the bag bottom). suspension cells, or insect cells, clearly showing the potential of these bioreactors (Lohr et al, 2009;Okonkowski et al, 2007;Tang et al, 2007;Weber et al, 2002).…”
Section: Liquid Shear Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Heights measured are shown as three circles piled (5, 12, and 22 mm above the bag bottom). suspension cells, or insect cells, clearly showing the potential of these bioreactors (Lohr et al, 2009;Okonkowski et al, 2007;Tang et al, 2007;Weber et al, 2002).…”
Section: Liquid Shear Stressmentioning
confidence: 99%
“…Various examples can be found for the cultivation of animal cells using bioreactors with wave-induced motion, demonstrating the possibility of adapting classical processes that use either roller bottles or stirred tank bioreactors to the cellbag method (Hundt et al, 2007;Lohr et al, 2009;Okonkowski et al, 2007;Tang et al, 2007;Weber et al, 2002). For the cultivation of adherent Madin-Darby canine kidney (MDCK) cells in an influenza vaccine production process, it has been observed that higher maximum cell densities can Correspondence concerning this article should be addressed to D. Thévenin at thevenin@ovgu.de.…”
Section: Introductionmentioning
confidence: 99%
“…The perfusion rate depends on the type and culture behavior of the cell line, the concentration of nutrients in the feed and the level of toxicity. This mode of operation has been used for the production of monoclonal antibodies (Banik and Heath, 1995;Tang et al, 2007; and recombinant proteins (AlRubeai et al, 1999;Avgerinos et al, 1990). An example of a 500 L industrial perfusion system for monoclonal antibody production by hyridoma is described by (Deo et al, 1996) where the operation continued for 15 to 35 days to achieve commercial production of antibodies with a cell density of >10 x 10 6 cell/mL.…”
Section: Perfusion Culturementioning
confidence: 99%
“…57 It operates in different culture modes, including perfusion, which can be performed using different cell-retention mechanisms for the high-efficient production of mAbs. 58 The combined advantages of a fully closed, disposable system with process monitoring capabilities (pH and DO) make the wave bioreactor highly attractive over traditional systems for animal cell culture, such as shake flasks and STR, 57 although with limitations in culture volume.…”
Section: Systems For Large-scale Productionmentioning
confidence: 99%